Application of Problem Based Learning Method in Entrepreneurship and Hygiene Sanitation with Flipped Classroom Strategy - Fadilla, Niki; Nurlaela, Luthfiyah; Maspiah, Maspiah (International Journal for Educational and Vocational Studies, 2019)
The post-millennial generation or currently known as the Z generation, is a generation born in the 2000s, a future generation born in the Internet era. These post-millennial generations don't like rigid rules, tend to think creatively and openly and are very easy to comment. An important point in dealing with the post-millennial generation by giving special directions for understanding ethics in social life. In the learning process, the post-millennial generation has visual characteristics, tries and sees the results of the process, wants the teacher as a facilitator, learning starts with "how", and is very easy to get information / knowledge. This is a challenge in determining the right learning strategy for them. Flipped Classroom learning strategy is a strategy designed by the teacher in preparing for learning before face to face in class / at home through learning videos then reflecting on the results of learning in the classroom with discussion and work on assignments (The Flipped Learning Network, 2014). Flipped classrooms require careful preparation so that learning videos that are made interesting, high quality, and can be understood by students without face to face. While students, on the other hand, must have access to an internet connection. With the problem based learning method it is expected that students/ vocational high school (SMK) students will be able to create something different to produce rewards in the form of money as well as personal satisfaction and freedom (Drucker, 1999). In entrepreneurship, students must understand the importance of maintaining health by maintaining and protecting food hygiene, through controlling environmental factors that can or may cause illness and health problems.